PEARL-21: SIX ROWED, HIGH YIELDING, HEAT STRESS RESISTANT, AND EARLY MATURING BARLEY CULTIVAR - AHMAD, J; AHSAN, A; MAKHDOOM, M; SHAMIM, S; GULNAZ, S; OWAIS, M; ASGHAR, S; MAHMOOD, A; RIAZ, M; SALEEM, M (Biological and Clinical Sciences Research Journal, 2024)
Pearl-21, an early maturing barley cultivar that was developed keeping in view the fluctuating climatic scenarios as drought stress is severely impairing the yield of crops in Pakistan. The exquisite genotypes were received from the International Center for Agricultural Research in the Dry Areas (ICARDA), Lebanon. The superior line was screened out from the international barley segregating population received from ICARDA. It was evaluated under code B-14035 in station yield trails for two years (2014-15 & 2015-16). It excelled by 15.26% and 7.38% in provincial barley yield trials during 2017-18 and 18.77% and 10.18% in national barley yield trials during 2018-19 in contrast to commercial checks Haider-93 and Sultan-17, respectively over four locations. It also presented encouraging results in rainfed yield trials. Pathological studies depicted that the proposed cultivar had exceptional resistance against rust diseases. Pearl-21 has plant height ranging from 95-99 cm with semi-erect growth habit both at the seedling and booting stage. It has a high tillering trend (140 productive tillers per meter). It took only 99-101 days to head while, 123-130 days for maturity. It bears 60-70 seeds per ear and has 34-38g thousand-grain weight. The prominent features it encompasses are drought and lodging tolerance and short duration. Due to encouraging steady performance for better grain yield, resistance against rusts, and quality Punjab Seed Council approved it in 2021 with the name “Pearl-21” for general cultivation in Punjab, Pakistan.